Effect of long-term proton pump inhibitors on phosphocalcium metabolism and bone mineral density - Hend Smaoui; Lassaad Chtourou; Dana Jallouli; Samar Ben Jemaa; Iheb Karaa; Mouna Boudabbous; Manel Moalla; Hela Gdoura; Leila Mnif; Ali Amouri; Rim Akrout; Fatma Ayadi; et al. (Future Science OA, 2024)
Aim: Although Proton pump inhibitors (PPIs) are well-tolerated, their long-term use may be associated with decreased bone mass. Methods: This is a case-control study including patients treated with PPIs (>1 year) and control subjects who have not received PPIs treatment. Results: A total of 90 patients and 90 matched controls were included. PPIs use was associated with hypocalcemia and hypomagnesemia. Vitamin D3 deficiency and hyperparathyroidism were associated with PPIs use. Long-term PPIs use was significantly associated with decreased bone density. Risk factors of decreased bone mineral density (BMD) included age >50 years, menopause, lack of sun exposure, double PPIs dose, daily intake, post-meal intake and association with a mucoprotective agent. Conclusion: Our results highlight the risk of decreased BMD in patients on long-term PPIs treatment.